An assessment of a co-rotational EAS brick element - Polat, Cengiz (Latin Amer J Solids Structures, 2010)
A locking-free formulation of 8-node brick element and its application is demonstrated. The Enhanced Assumed Strain (EAS) method is used to alleviate the locking problems. A co-rotational formulation is adopted in the formulation, thus geometric nonlinearity is taken into account via rotation of the local coordinate system. Several benchmark problems are analyzed to demonstrate the efficiency of the element.
Keywords: brick element; co-rotational formulation; EAS method